TAFSIR PLURALISME AGAMA DALAM BUKU FIQIH LINTAS AGAMA: KAJIAN DAN KRITIK - Achmad Yaman (STAI DI AL-HIKMAH, 2023)
The book Interfaith Fiqh: Building an Inclusive-Pluralist Society is one of the books published by The Paramadina Foundation in collaboration with The Asia Foundation. This research aims to show any irregularities or irregularities in the interpretation of the Koran by the authors, especially sensitive matters and principles in Islamic Sharia. This research method uses a critical comparative study method of the authors' interpretations in explaining Religious Pluralism. The authors use a new interpretive approach, according to them, which is known as the Hermeneutic Method, namely a method that is contextual and interprets everything, including the Koran, in a liberal, free way and even seems haphazard without maintaining the sanctity of the Islamic holy book. Based on the research results, it can be concluded that the authors' interpretation of Religious Pluralism using a Hermeneutic approach is not in accordance with the mainstream of Islamic teachings or the interpretive methodology of the ulama whose knowledge and understanding of the Qur'an are beyond doubt.